PENGARUH HARGA, KUALITAS PELAYANAN, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA PENGGUNA GO-RIDE DI KOTA SAMARINDA - Rahmi Ariani Kartini (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
The internet is an information technology that is growing very rapidly because the internet has become a necessity and also provides convenience in everyday life, one of which is online transportation. Go-Ride is an online transportation service that uses the internet to make it easier for people to carry out activities safely and comfortably, so that consumers are loyal to the products offered.This study aims to determine the effect of price, service quality, and promotion on customer loyalty for Go-Ride users in Samarinda. Price (X1), Service Quality (X2), Promotion (X3) are used as independent variables while Customer Loyalty (Y) is the dependent variable. Primary data were obtained by conducting interviews with 100 respondents using a questionnaire. Data were analyzed using multiple linear regression analysis techniques with the help of statistical software SPSS version 20.The results of this study indicate that service quality and promotion partially have a significant effect on customer loyalty, while price does not partially have a significant effect on customer loyalty to Go-Ride users in Samarinda.